2022
DOI: 10.3390/nano12132224
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Nanocarrier—Cubosomes, Characterization, and Applications

Abstract: The impact of nanotechnology on the exponential growth of several research areas, particularly nanomedicine, is undeniable. The ability to deliver active molecules to the desired site could significantly improve the efficiency of medical treatments. One of the nanocarriers developed which has drawn researchers’ attention are cubosomes, which are nanosized dispersions of lipid bicontinuous cubic phases in water, consisting of a lipidic interior and aqueous domains folded in a cubic lattice. They stand out due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 146 publications
0
8
0
Order By: Relevance
“…The Miller indices (hkl) associated with these peaks are (110), (111), (200), (211), (220), and (221), respectively [ 30 , 31 ]. Considering these results, the phytantriol-based formulations can be considered cubosomes, which is expected for nanoparticles prepared using this polar lipid [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Miller indices (hkl) associated with these peaks are (110), (111), (200), (211), (220), and (221), respectively [ 30 , 31 ]. Considering these results, the phytantriol-based formulations can be considered cubosomes, which is expected for nanoparticles prepared using this polar lipid [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In pharmaceutical products, monoolein can be used as emulsifier, solubilizer, absorption enhancer, and in oral drug delivery systems, such as those proposed in this work [ 7 ]. Phytantriol is also nontoxic and biocompatible and is widely used in the cosmetic industry [ 9 ]. Phytantriol was considered nontoxic in acute oral testing and not genotoxic while having low skin penetration [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 Their unique characteristics, such as mechanical strength, biodegradability, moisture retention, cellular interactions, antimicrobial properties, gel-forming capabilities, and fibrous structure, contribute to their versatility and potential in the field of tissue engineering and regenerative medicine. 17,18 For instance, silk fibroin is renowned for its remarkable mechanical strength, biocompatibility, and biodegradability. 19 Incorporating silk fibroin into BNCs not only imparts structural integrity and support to the regenerated tissue but also ensures gradual degradation of the BNC scaffold, allowing the regenerated tissue to assume its functionality.…”
Section: Introductionmentioning
confidence: 99%
“…In the study reported herein, we use lipid nanocarriers of internal cubic symmetry (cubosomes) for the encapsulation and delivery of TDM. Similar to liposomes, cubosomes are based around the fundamental structure of a lipid bilayer.…”
Section: Introductionmentioning
confidence: 99%
“…15 The efficacy of lipid nanoparticles in vaccine delivery has been topically exemplified by the BioNTech/ Pfizer and Moderna COVID-19 vaccines, both of which utilize a lipid nanoparticle system to deliver the mRNA. 16,17 In the study reported herein, we use lipid nanocarriers of internal cubic symmetry (cubosomes) 18 for the encapsulation and delivery of TDM. Similar to liposomes, cubosomes are based around the fundamental structure of a lipid bilayer.…”
mentioning
confidence: 99%